Untamed : the wild life of Jane Goodall - Silvey, Anita (National Geographic, 2015)
"This biography for children will trace Goodall's life, but each chapter will also focus on two or more the chimpanzees that she observed, with information in sidebars about these particular animals. Along with biographical details, the book will explorethe ethical issues that surround Goodall's work and show what has changed in our understanding of Great Apes. What do we know today about these animals in terms of language, speech, tool use, and DNA? How has sophisticated technology - GPS systems, Satellite imagery, portable digital microphones - been used to gain new information about animal populations."--